New data on the Vegavis iaai holotype from the Maastrichtian of Antarctica - Acosta Hospitaleche, Carolina Ileana Alicia; Worthy, Trevor H. (Cretaceous Research)
Vegavis iaai has key importance as the most complete of the few neornithine birds known from the Cretaceous, yet its phylogenetic relationships remain controversial. To seek new data to resolve this problem, we fully extracted the skeleton of the holotype MLP 93-I-3-1 from the sedimentary matrix it had been found in to enable new direct observations on its osteology. We provide the first detailed descriptions of the synsacrum confirming the presence of fifteen ankylosed vertebrae, and of the cervical and thoracic vertebrae for this specimen, and elaborate on the available descriptions of the coracoid, humerus, radius, and all pelvic limb elements. A well-marked proximo-caudal fossa of the femur, described as a diagnostic character for Vegavis from observations of the referred specimen, is shallow and poorly defined in the holotype. The skeleton reveals a mix of features supporting enhanced diving ability for the bird. We make three-dimensional scans and high-quality images of all bones in the holotype available for further comparisons. Fil: Acosta Hospitaleche, Carolina Ileana Alicia. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina Fil: Worthy, Trevor H. Flinders University.; Australia